Bipolar disorder - Peacock, Judith, 1942- (Minnetonka, MN : Life Matters, 2000)
Explains bipolar disorder including its types, diagnosis, and treatment and offers strategies for dealing with this illness in oneself and others.
Includes bibliographical references (p. 61) and index.
Keywords: Manic-depressive illness -- Juvenile literature; Depression, Mental -- Juvenile literature; Affective disorders -- Juvenile literature; Manic-depressive illness; Depression, Mental; Affective disorders